Hybrid Learning and Education Second International Conference, ICHL 2009, Macau, China, August 25-27, 2009, Proceedings - Wang, Fu Lee; Fong, Joseph; Zhang, Liming; Lee, Victor K. S. (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the second International Conference on Hybrid Learning, ICHL 2009, held in Macau, China, in August 2009. The 38 revised full papers presented together with one keynote lecture were carefully reviewed and selected from 149 submissions. The papers are organized in topical sections on interactive hybrid learning systems, effective content development, pedagocical and psychological issues, outcome based teaching and learning, student prospects, improved flexibility of the learning process, computer supported collaborative learning, hybrid learning experiences, practices borderless education, digital library and content management, organizational framework and institutional policy, and learning theory.